(untitled) (The Review of Diabetic Studies, 2024)
Low back pain (LBP) poses a significant global health challenge, affecting up to 80% of individuals in their lifetime and often resulting in functional impairment, socioeconomic consequences, and psychological distress. This study investigates the effectiveness of various physiotherapy techniques in managing chronic low back pain (CLBP), defined as pain lasting longer than 12 weeks. It explores how these interventions impact patients’ pain levels, functional abilities, and overall quality of life. With a focus on multidisciplinary approaches, including exercise, manual therapy, and reflex therapy, the research emphasizes the need for tailored treatment strategies that cater to diverse patient demographics. The study also assesses preventative measures against CLBP and aims to identify optimal treatment protocols to enhance recovery and minimize recurrence. Findings highlight that while conservative treatments, including physical therapy and medication, can provide symptomatic relief, a combined approach integrating self-management strategies and psychosocial support appears most beneficial for long-term outcomes. The necessity for public health programs and improved healthcare pathways to educate and support patients in managing low back pain effectively is underscored as essential for future strategies. These insights contribute to the evolving landscape of LBP management and advocate for evidence-based interdisciplinary care.